Food waste pyrolysis by traditional heating and microwave heating: A review. (15th September 2022) - Li, Hua; Xu, Jialiang; Mbugua Nyambura, Samuel; Wang, Jufei; Li, Chao; Zhu, Xueru; Feng, Xuebin; Wang, Yongjian
Highlights: Illustration of the heating mechanism of traditional heating and microwave heating. Overview of the effects of factors on food waste pyrolysis. Detailed summarization and review of latest research of food waste pyrolysis. Techno-economic analysis and Future perspectives on food waste pyrolysis. Abstract: Food waste has extensive sources and can be produced in every stage of the supply chain. Traditional landfills and incineration of food waste are deteriorating our environment. As a greener technique, pyrolysis has attracted increased interest because it provides a promising way to convert billion tons of food waste into value-added products. The main pyrolysis methods can be divided into traditional heating and microwave heating. Their distinct heating mechanism can significantly affect the pyrolysis process. Based on this, this paper summarized and overviewed the heating mechanism and effect factors of both traditional heating and microwave heating pyrolysis. Moreover, the latest studies of food waste pyrolysis in traditional and microwave heating are also reviewed from biochar, bio-oil, and biogas. This paper aims to review the effects of heating methods on food waste pyrolysis products and yield distributions, which can be of great importance to the pyrolysis application and further investigation. Moreover, the techno-economic analysis is also involved in this review to provide a reference for pyrolysis industrialization. Lastly, this paper discussed the existing challenges and future implications for the future development of food waste pyrolysis, where the pretreatment needs more optimization and studying.